Peluang Diplomasi Komersial Pemerintah Indonesia dalam Mendorong Energi Bersih - Damayanti, Larassita (Review of International Relations, 2025)
This article discusses the role and opportunities for developing the clean energy sector through commercial diplomacy by the Indonesian government. The selection of this issue is based on the untapped potential of clean energy. In addition, the clean energy market at the regional and global levels is potential, considering that countries are still highly dependent on fossil energy. At the same time, Indonesia has a diverse range of clean energy sources. In this case, if the sources is developed well, then it help Indonesia as a key player in the clean energy sector. This paper uses the theory of commercial diplomacy with a focus on trade promotion and advocacy. The analysis shows that multilateral cooperation schemes such as ASEAN, RCEP, and APEC, which also focus on clean energy, have not been fully utilized by the Indonesian government. Furthermore, during the Paris Agreement negotiations, Indonesia did not express its interests, the limitations of clean energy infrastructure, and the availability of financing for the clean energy sector. This has resulted in a significant gap in achieving clean energy targets by 2025, as outlined in the Nationally Determined Contribution document.